2011
DOI: 10.1111/j.1439-0329.2011.00751.x
|View full text |Cite
|
Sign up to set email alerts
|

A molecular toolkit for population genetic investigations of the ash dieback pathogen Hymenoscyphus pseudoalbidus

Abstract: The recently described ascomycete fungus Hymenoscyphus pseudoalbidus (anamorph: Chalara fraxinea) causes the current dieback of ash (Fraxinus excelsior) in large parts of Europe. The origin of this species and its relation to the native cryptic species Hymenoscyphus albidus are still enigmatic. The spatiotemporal pattern of the epidemic is typical for an introduced invasive species. However, the presence of two cryptic species indicates that hybridization or mutation might have been involved in driving speciat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 50 publications
1
57
0
Order By: Relevance
“…The two Hymenoscyphus species may be distinguished due to the presence of a specific microsatellite locus and varied allele lengths (Gross et al. ). In contrast to H. albidus, pathogenic properties of H. pseudoalbidus (Bakys et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two Hymenoscyphus species may be distinguished due to the presence of a specific microsatellite locus and varied allele lengths (Gross et al. ). In contrast to H. albidus, pathogenic properties of H. pseudoalbidus (Bakys et al.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Gross et al. () ascertained great variability of pathogen isolates with the use of microsatellite markers. Zhao et al.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic analyses will be instrumental in devising strategies to cope with an increased pressure from established and new diseases as a result of better suitability of the climatic conditions and/or more intense and farreaching trade (Bawa and Dayanandan 1998;Archie et al 2008;Jombart et al 2011). For example, there is genetic evidence that some ash trees (Fraxinus excelsior) in Denmark are resistant against the emerging fungal pathogen Chalara fraxinea (McKinney et al 2011;Kjaer et al 2012), which is now reported to cause ash dieback throughout Europe, from Poland to France and from Sweden to Switzerland (Bengtsson et al 2012;Gross et al 2012). For this pathosystem, there are also data on the genetic variability of the pathogen in lowland vs. highland Poland (Kraj et al 2012) and in the Åland islands, mainland Finland, Estonia and Latvia (Rytkönen et al 2011).…”
Section: Interdisciplinarity Stakeholder Involvement and Trade-offsmentioning
confidence: 99%
“…The genetic variability between populations may provide information on the recent history and movement of the pathogens (Gross et al, 2012). Microsatellite analysis provided some insight into the spread of M. fijiensis in the country, despite the limited sample size.…”
Section: Discussionmentioning
confidence: 99%